G
godgog
![](https://blog.hocmai.vn/wp-content/uploads/2017/07/hot.gif)
![](https://blog.hocmai.vn/wp-content/uploads/2017/07/hot.gif)
1.[TEX]log_2(x-\sqrt{x^2-1}). log_3(x \sqrt{x^2-1})=log_6(x-\sqrt{x^2-1})[/TEX]
2.[TEX]log_2(1+\sqrt{x})=log_3(x)[/TEX]
3.[TEX]2log_6(\sqrt{x}+\sqrt[4]{x})=log_4(x)[/TEX]
Ở bài 3 là căn bậc 4 của x nha.thanks
2.[TEX]log_2(1+\sqrt{x})=log_3(x)[/TEX]
3.[TEX]2log_6(\sqrt{x}+\sqrt[4]{x})=log_4(x)[/TEX]
Ở bài 3 là căn bậc 4 của x nha.thanks
Last edited by a moderator: